Evaluation of the Design and Didactic Development of Three Blended Learning Subjects. A Pilot Plan of the Faculty of Social Sciences at the Universidad Nacional, Costa Rica - Araya-Muñoz, Isabel; Fonseca-Argüello, Matilde; Majano-Benavides, Jilma; Ugalde-Villalobos, María Eugenia (Revista Electrónica Educare, 2019)
This article presents the results of the exploratory pre-experimental evaluation process of design and didactic development of three subjects using the semi-distance learning model or blended learning, through a pilot application plan in bachelor’s degrees of the Faculty of Social Sciences at the Universidad Nacional de Costa Rica. First, the blended learning model was applied. Later, scientific information was collected through a survey of students, a panel discussion with teachers, and an analysis of the contents of the study programs. The results show that the interaction between students and teachers increases through their favorite activities such as forums and tasks, which strengthen the individual and collaborative work and the reflective analysis, aspects that favor building learnings. Various lines of research arise from this study; they are necessary to go in depth, specifically, in quasi-experimental studies. Some of these lines are the following: to show the assumptions of the blended learning and educational factors that favor the development of meaningful learning for the student; to determine what the cognitive processes, carried out in mixed learning environments, are; and to test the positive relationship between the student’s academic performance and the semi-distance didactics.